Development of water and energy efficient environment friendly easy care finishing by foam coating on stretch denim fabric. (15th June 2017) - Sarwar, Nasir; Mohsin, Muhammad; Bhatti, Amanat Ali; Ahmmad, Syed Waqas; Husaain, Azhar
Abstract: Nowadays, intensive use of technology during textile manufacturing is responsible for making the processes more energy intensive. Most of the countries in the world are also facing shortage of pure drinking water. During conventional textile processing such as padding technique, high amount of water is needed to dissolve and apply the required chemicals onto the fabric for the desired performance. The excess usage of water is responsible for the increase in the processing cost as lengthy drying step is needed. In addition, available drinking water is reduced and enormous water effluent is also generated. In this research new environment friendly, formaldehyde free, easy care finishing process is developed by low pick up foam coating technique for stretch denim. The foam stability of the easy care finish was successfully improved by optimizing the thickener and foaming agent. Treated fabric performance was assessed by measuring the crease recovery angle, dry and wet rubbing fastness, shade change after washing, tear strength retention, stretch % and elongation %, stiffness, air permeability and anti microbial. Cost, energy and water efficient foam coated fabric exhibited similar and in some cases improved results as that of padded fabric. Highlights: Energy and water efficient foam technology for stretch denim is developed. Environment friendly zero formaldehyde cross-linker was applied by foam technique. Thickener and foaming agent quantity was also optimized for best results. Foam coated fabric exhibited similar or better performance than padded fabric. Less amount of chemical and less water effluent is generated by foam technique.